Optical pulse Self-compressor combined the Nonlinear coupler with Backward Raman fiber amplifier - Bien, Chu Van; Quy, Ho Quang; Lanh, Chu Van; Luu, Mai Van; Thanh, Thai Doan (Communications in Physics, 2012)
Based on the nonlinearity of the nonlinear optical coupler (NOC) and the amplifying capacity of the backward Raman fiber amplifier (PBRFA), a new optical system to compress the optical pulse (optical pulse self-compressor: OPSC) is proposed. Using the expressions describing relationship between output intensities from both output ports and input one of NOC and the expression describing the amplification of the PBRFA, the compressing process of the optical pulse propagating through OPSC is simulated. The results show that the peak of optical pulse will be enhanced and the duration of optical pulse will be reduced significantly, and the shape of input pulse is completely compressed with certain efficiency. It means the optical pulse is self-compressed without the pump pulse.